2006
DOI: 10.1175/mwr3331.1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Clouds and Rain Using a z-Coordinate Nonhydrostatic Model

Abstract: The most common option for numerical models of the atmosphere is to use model layers following the surface of the earth, using a terrain-following vertical coordinate. The present paper investigates the forecast of clouds and precipitation using the z-coordinate nonhydrostatic version of the Lokalmodell (LM-z). This model uses model layers that are parallel to the surface of the sphere and consequently intersect the orography. Physical processes are computed on a special grid, allowing adequate grid spacing ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…There is a strong indication that the interest in quasi-horizontal coordinates is on the increase in recent years, originally sparked by the shaved cells approach of Adcroft et al (1997), and used subsequently by Steppeler et al (2006) and Walko and Avissar (2008). The standard step-topography eta has been used in more recent efforts as well; note Marshall et al (2004), and in particular Russell (2007).…”
Section: Dynamics: Sloping Stepsmentioning
confidence: 99%
“…There is a strong indication that the interest in quasi-horizontal coordinates is on the increase in recent years, originally sparked by the shaved cells approach of Adcroft et al (1997), and used subsequently by Steppeler et al (2006) and Walko and Avissar (2008). The standard step-topography eta has been used in more recent efforts as well; note Marshall et al (2004), and in particular Russell (2007).…”
Section: Dynamics: Sloping Stepsmentioning
confidence: 99%
“…Good et al (2014) demonstrated the undesirable influence of its nonorthogonality using idealized test cases. With realistic forecasting cases, the property of the terrain-following approach was considerably sensitive for precipitation or temperature, particularly near high mountains (Steppeler et al 2006(Steppeler et al , 2011(Steppeler et al , 2013. Satomura (1989) introduced generated coordinates, whose orthogonality was higher, to an atmospheric model in order to reduce the errors associated with the terrain-following approach.…”
Section: Introductionmentioning
confidence: 99%
“…A cut-cell approach with z-coordinates, which has recently been investigated (e.g., Adcroft 2013; Adcroft et al 1997;Good et al 2014;Lock et al 2012;Steppeler et al 2002Steppeler et al , 2006Steppeler et al , 2011Steppeler et al , 2013Walko and Avissar 2008;Yamszaki and Satomura 2010;Yamazaki et al 2016), is that topography is approximated using pricewise linear or bilinear functions. Although topography can be more accurately represented, the method requires complex boundary conditions for the pressure or the velocities on topographical surface.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they concluded that the shaved cell method is the most conducive to smooth and accurate topography representation, although the partial cell method is a good compromise for shallow slopes. The shaved cell method has also been applied to an atmospheric model by Steppeler et al (2002) and Steppeler et al (2006). Steppeler et al (2002) showed that the shaved cell method reproduces flow over a gently sloping bell-shaped mountain as precisely as a model using the terrain-following coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Steppeler et al (2002) showed that the shaved cell method reproduces flow over a gently sloping bell-shaped mountain as precisely as a model using the terrain-following coordinates. In Steppeler et al (2006), tests of precipitation forecasts over realistic mountains were performed using the shaved cell model, and compared with those using the terrain-following model. However, they did not clearly show if the shaved cell method is adaptive to steep mountains.…”
Section: Introductionmentioning
confidence: 99%